2022
DOI: 10.1111/ped.14940
|View full text |Cite
|
Sign up to set email alerts
|

All‐cause mortality in a pediatric intensive care unit at a teaching hospital in Amman, Jordan

Abstract: Background The aim of this study was to describe the main causes of admission to a general pediatric intensive care unit (PICU), and examine the main causes of mortality in this patient population. In addition, we describe the percentage of patients who died following a failed cardiopulmonary resuscitation (CPR) versus do not resuscitate (DNR) orders. Methods This was a retrospective, cohort study with a chart review of admissions and mortality cases that occurred in the PICU. Mortality rates in pediatric admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In countries with available resources, overall mortality in a general PICU can be as low as 2.39%, while in developing countries the reported rates are much higher (16.5–45.5%). 1 Gilleland and Parshuram 2 reported that timely conversations about death as a possible outcome of PICU are an important part of high-quality intensive care. Informed conversations require preparation to provide families with the best available objective information.…”
Section: Introductionmentioning
confidence: 99%
“…In countries with available resources, overall mortality in a general PICU can be as low as 2.39%, while in developing countries the reported rates are much higher (16.5–45.5%). 1 Gilleland and Parshuram 2 reported that timely conversations about death as a possible outcome of PICU are an important part of high-quality intensive care. Informed conversations require preparation to provide families with the best available objective information.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, comorbidity was one of the determinant factors contributing to pediatric patients' mortality in PICU. This finding is supported by studies conducted in Jordan ( 23 ) and India ( 34 ). Comorbidities have been shown to have a significant impact on the clinical course, complications rate, and outcomes in the ICU.…”
Section: Discussionsupporting
confidence: 72%
“…In our review, two articles stated that the use of mechanical ventilators was the factor for pooled mortality of pediatric patients at PICU. This review is supported by studies conducted in Jordan ( 23 ) and the Netherlands ( 28 ). The possible explanation is that most patients who require mechanical ventilators are more critical than those who do not, and it stays in for a couple of days, thereby increasing mortality.…”
Section: Discussionmentioning
confidence: 84%
“…Most children ultimately diagnosed with CHD were referred for evaluation based on murmur or cyanosis ( 13 ). CHD is an important factor in both neonatal and childhood mortality in Jordan ( 17 , 18 ). Fetal echocardiography is available at some referral centers ( 19 ).…”
Section: Introductionmentioning
confidence: 99%